1998
DOI: 10.1136/hrt.80.6.583
|View full text |Cite
|
Sign up to set email alerts
|

Extent and severity of atherosclerotic involvement of the aortic valve and root in familial hypercholesterolaemia

Abstract: Conclusions-In patients with familial hypercholesterolaemia, aortic stenosis is common in homozygotes, and aortic root involvement is always present despite the lower CYS than in heterozygotes. It appears to be determined by short term exposure to high cholesterol concentrations in early life. Conversely, aortic root and valve involvement are rare in heterozygotes and occur only with severe, prolonged hypercholesterolaemia, possibly accelerating age related degenerative effects. (Heart 1998;80:583-590)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 23 publications
1
69
2
1
Order By: Relevance
“…106 Transthoracic and transesophageal echocardiography can be used to quantify the severity of aortic valve and supra-aortic disease. 107 Magnetic resonance imaging can also be used as an alternative to CTA to study the aorta and to plan possible surgical interventions.…”
Section: Natural History Of Homozygous Fh and Subclinical Atherosclermentioning
confidence: 99%
“…106 Transthoracic and transesophageal echocardiography can be used to quantify the severity of aortic valve and supra-aortic disease. 107 Magnetic resonance imaging can also be used as an alternative to CTA to study the aorta and to plan possible surgical interventions.…”
Section: Natural History Of Homozygous Fh and Subclinical Atherosclermentioning
confidence: 99%
“…Indeed, valvular AS and supravalvular AS are known complications in patients with familial hypercholesterolemia, and sclerotic changes in the aortic valve are ubiquitous in homozygotes and common in heterozygotes. 27,28 It is thus a reasonable hypothesis that statins, which are effective in treating hypercholesterolemia and reducing coronary events, may also be effective in reducing the rate of progression of AS. Several retrospective studies have supported this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the rate of aortic valve surgery was 24% in homozygous FH patients 39) . Groups of researchers have demonstrated that cholesterol levels and duration after diagnosis of FH are associated with aortic stenosis 40,41) . However, the relation between cholesterol exposure and aortic stenosis…”
Section: Genetic Characteristicsmentioning
confidence: 99%